Low-thermal-conductivity anti-sintering thermal barrier coating material as well as preparation method and application thereof

By using solid solution doping and second phase doping technologies of ZrO2, Y2O3, Yb2O3, Gd2O3, Nd2O3 and Al2O3 in the thermal barrier coating material, a stable cluster structure and efficient photon scattering are formed, which solves the problem of poor high thermal conductivity and sintering performance in high-temperature environments, and the combination of low thermal conductivity and good sintering performance is achieved, which is suitable for thermal protection of high-temperature components.

CN119707488AInactive Publication Date: 2025-03-28XI AN JIAOTONG UNIV

Patent Information

Application Number
CN202510213123.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing thermal barrier coatings have problems such as high thermal conductivity, poor sintering resistance and insufficient phase stability in high temperature environments, which limit their application in high temperature service.

Method used

A low thermal conductivity and thermal barrier coating material is used, and its composition includes 82.3%~92.45% ZrO2, 3.5%~7.5% Y2O3, 2.0%~3.0% Yb2O3, 1.5%~4.0% Gd2O3, 0.5%~2.0% Nd2O3 and 0.05%~1.2% Al2O3. Through the combination of solid solution doping and second phase doping, a stable cluster structure and efficient photon scattering are formed, reducing thermal conductivity and improving anti-sintering performance.

Benefits of technology

It achieves a combination of low thermal conductivity and good sintering resistance in high-temperature environments, significantly improves the phase stability and thermal protection of the coating, and is suitable for thermal protection of high-temperature components such as aircraft engine turbines, rocket engine tail nozzles or rocket engine combustion chambers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707488A_ABST
    Figure CN119707488A_ABST
Patent Text Reader

Abstract

The invention discloses a low-thermal-conductivity anti-sintering thermal barrier coating material as well as a preparation method and application thereof, and belongs to the technical field of coating materials. The low-thermal-conductivity anti-sintering thermal barrier coating material comprises a base phase oxide (ZrO2), four groups of solid solution doped rare earth oxides (Y2O3, Yb2O3, Gd2O3 and Nd2O3) and a group of second phase doped oxides (Al2O3), the four groups of solid solution doped rare earth oxides exist in ZrO2 in a solid solution form to form a ZrO2 solid solution, and Al2O3 is doped in the ZrO2 solid solution in a second phase form; wherein the ion radiuses and cation valences of Yb2O3, Gd2O3 and Nd2O3 are different from the cation radiuses and valences of the base phase oxide or the main stable oxide (Y2O3). The low-heat-conduction anti-sintering thermal barrier coating material is sprayed on the surface of a base body or other coatings, and compared with a coating formed by a traditional YSZ material, the formed thermal barrier coating has the low heat conduction performance and the anti-sintering performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of coating materials, and in particular relates to a low thermal conductivity sintering resistant thermal barrier coating material and a preparation method and application thereof. Background Art

[0002] Thermal barrier coatings are very important thermal protection coatings on the surfaces of hot end components of advanced gas turbines and aircraft engines. Their excellent heat insulation and oxidation resistance can significantly improve the efficiency and service life of equipment. At present, the ceramic top layer of thermal barrier coatings mainly uses traditional ceramic materials such as yttria stabilized zirconia (Yttria Stabilized Zirconia; YSZ; ZrO 2 -3.5~4.0 mol% Y 2 O 3 ), also known as (8wt% Y 2 O 3 -ZrO 2 It is a kind of 2 O 3 ) as a stabilizer to change the zirconium oxide (ZrO 2 ) phase transition temperature range, thus producing stable cubic and tetragonal ceramic materials at room temperature. YSZ and ZrO 2 Compared with low thermal conductivity and high thermal expansion coefficient, plasma spraying or physical vapor deposition can make the coating have a certain layered or columnar structure, and show better thermal insulation or strain tolerance; YSZ can also be prepared by different methods to obtain YSZ powders with different structures such as nano-agglomeration and hollow spherical shells, which also show better thermal insulation than traditional solid YSZ materials in practical applications. However, YSZ above 1200℃ will cause internal phase change of the material and sintering rigidification of the coating structure in a long-term service environment. Due to the increase in the content of the monoclinic phase (M phase) with higher thermal conductivity with high-temperature annealing time and the high-temperature sintering of ceramics, the thermal conductivity of the coating will increase with the decrease of porosity, and the low thermal conductivity advantage of YSZ will gradually disappear.

[0003] Currently, increasing the service temperature of hot end components is the most powerful measure to improve equipment efficiency, but higher temperatures will also lead to more problems, such as higher stress, increased material phase instability and thermal oxidation, leading to premature failure of hot end components.

[0004] In order to solve the problems of traditional YSZ materials, researchers proposed to dope ZrO 2 At present, the proposed multi-rare earth oxide doped modified ZrO 2 The design idea of ​​the system is: the main stable oxide (Y 2 O 3) is used to stabilize the tetragonal phase; a type of doped oxide cation radius is smaller than the main stabilizing oxide and the base phase oxide (ZrO 2 ); Another type of doped oxide cation radius is larger than the main stable oxide and the base phase oxide, such as 2 mol% Gd 2 O 3 -4.5 mol% Y 2 O 3 -93.5 mol% ZrO 2 Binary doped zirconia material, 5mol% Nd 2 O 3 – 5 mol% Yb 2 O 3 -3mol% Ta 2 O 5 – 87 mol% ZrO 2 Ternary doped zirconia material, 2 mol% Gd 2 O 3 – 5.8 mol% Y 2 O 3 – 2 mol% Yb 2 O 3 – 90.2 mol% ZrO 2 Ternary doped zirconia material, 8 mol% Y 2 O 3 - 1.25 mol% Yb 2 O 3 - 1.25 mol%Sc 2 O 3 - 1.25 mol% Nd 2 O 3 – 1.25 mol% Gd 2 O 3 – 87 mol% ZrO 2 Five-element doped zirconia materials. These methods are to add several types of rare earth oxides to YSZ, introduce lattice distortion and segregation defects based on cation size mismatch, thereby effectively reducing the thermal conductivity of the material, improving the phase stability of YSZ, and improving the sintering resistance. Although these methods can improve some of the performance of the material, there are still problems such as high thermal conductivity, unstable defects and clusters, and easy sintering. In addition, when serving at high temperatures, YSZ and multi-element rare earth doped ZrO 2 The infrared radiation of thermal barrier coatings is limited, which restricts their application in high temperature environments. Therefore, it is urgent to develop thermal barrier coatings with lower thermal conductivity and better sintering performance. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a low thermal conductivity sintering-resistant thermal barrier coating material and its preparation method and application, so as to solve the technical problems of poor high-temperature phase stability of the existing thermal barrier, high thermal conductivity of the coating and poor sintering resistance.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The first aspect of the present invention discloses a low thermal conductivity anti-sintering thermal barrier coating material, which comprises 82.3% to 92.45% ZrO in molar percentage. 2 , 3.5%~7.5% Y 2 O 3 , 2.0%~3.0% Yb 2 O 3 1.5%~4.0% Gd 2 O 3 , 0.5%~2.0% Nd 2 O 3 and 0.05%~1.2% Al 2 O 3 ; Among them, Y 2 O 3 , Yb 2 O 3 , Gd 2 O 3 and Nd 2 O 3 Both exist in the form of solid solution in ZrO 2 In the formation of ZrO 2 Solid solution, Al 2 O 3 It is doped into ZrO as a second phase 2 In solid solution; Gd 2 O 3 and Nd 2 O 3 The sum of the molar percentages of Yb 2 O 3 The molar percentage ratio of Al is 1.0~2.0; 2 O 3 The particle size is 0.75~1.25 μm.

[0007] Preferably, ZrO 2 In solid solution, ZrO 2 The content of monoclinic phase is less than 2.0%.

[0008] Preferably, the low thermal conductivity anti-sintering thermal barrier coating material is a nearly spherical powder with a particle size of 10 to 145 μm.

[0009] The second aspect of the present invention discloses a method for preparing the above-mentioned low thermal conductivity anti-sintering thermal barrier coating material, wherein ZrO 2 , Y 2 O 3 , Yb 2 O 3 , Gd 2 O 3 and Nd 2 O 3 After the powders are mixed, they are ball-milled for the first time to obtain premixed powders. Al is added to the premixed powders. 2 O 3 After the powders are mixed, they are ball-milled for the second time to obtain mixed powders, which are then sintered by a solid phase method to obtain a low thermal conductivity sintering-resistant thermal barrier coating material.

[0010] Preferably, wet ball milling is adopted, zirconium oxide balls are used in the ball milling process, and anhydrous ethanol is used as the dispersion medium.

[0011] Preferably, the conditions for the first ball milling are: ball milling at a speed of 250-300 r / min for 3-4 h; and the conditions for the second ball milling are: ball milling at a speed of 100-150 r / min for 30 min.

[0012] The third aspect of the present invention discloses a low thermal conductivity sintering resistant thermal barrier coating, which is formed by spraying the above-mentioned low thermal conductivity sintering resistant thermal barrier coating material on a substrate or other coating surface.

[0013] Preferably, the thickness of the low thermal conductivity anti-sintering thermal barrier coating is 50-350 μm.

[0014] Preferably, the thermal conductivity of the low thermal conductivity anti-sintering thermal barrier coating at 25° C. to 225° C. is less than 0.7 W / (m·K).

[0015] The fourth aspect of the present invention discloses the application of the above-mentioned low thermal conductivity sintering-resistant thermal barrier coating in the thermal protection of aircraft engine turbines, rocket engine tail nozzles or rocket engine combustion chambers.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a low thermal conductivity anti-sintering thermal barrier coating material, 1) in terms of composition, the base phase oxide ZrO 2 , solid solution doped rare earth oxide Y 2 O 3 , Yb 2 O 3 , Gd 2 O 3 and Nd 2 O 3 And the second phase doped oxide Al 2 O3 Together, Y 2 O 3 and Yb 2 O 3 Can effectively stabilize tetragonal and cubic ZrO 2 Crystal structure, Yb 2 O 3 , Gd 2 O 3 and Nd 2 O 3 It can reduce the thermal conductivity of the material and improve the sintering resistance of the material. The specially added Al with a particle size of 0.75~1.25 μm 2 O 3 As a second phase dopant, it will segregate at the grain boundary, and its size is close to the infrared radiation wavelength region (1~5 μm), which can effectively reduce photon diffusion, and Al 2 O 3 The lower refractive index can produce stable photon scattering at the interface of the composite material with higher reflectivity, which generally hinders the diffusion of photons inside RSZ4Y, thereby reducing the overall thermal conductivity of the material. 2 O 3 The doping amount of Nd is 3.5%~7.5%, which can stabilize the phase and promote cluster formation, reducing thermal conductivity; 2 O 3 The doping amount of Yb is 0.5%~2.0%, which is beneficial to reduce thermal conductivity, promote cluster formation, inhibit grain growth, improve phase stability and increase thermal expansion coefficient; 2 O 3 The doping amount is 2.0%~3.0%, Yb 2 O 3 The doping amount of Gd 2 O 3 、Nd 2 O 3 The ratio of the sum of the doping amounts is 1~2.0, which can ensure that ZrO 2 Crystal stability; Gd 2 O 3 The doping amount of Al is 1.5%~4.0%, which will not affect its advantage of reducing the thermal conductivity of the material; 2 O 3 The doping amount is 0.05%~1.2%, which can balance the overall low thermal conductivity and anti-sintering performance of the material. 3) In terms of structure, Y 2 O 3 , Yb 2 O 3 , Gd 2 O 3 and Nd 2 O 3 Both exist in the form of solid solution in ZrO2 In the case of ZrO 2 The crystal phase promotes cluster formation, reduces thermal conductivity and improves sintering resistance; Al 2 O 3 Doped in ZrO as a second phase 2 In the solid solution, the fracture toughness of the material as a whole can be improved, taking into account the overall sintering resistance and comprehensive low thermal conductivity of the material as a whole; the low thermal conductivity sintering-resistant thermal barrier coating material finally formed has nano-scale defect clusters and Al 2 O 3 Particles. Sintering tests and SEM morphology prove that compared with traditional YSZ materials, the coating prepared by the material of this method has stable phase and mechanical properties, lower thermal conductivity, lower porosity decrease rate, better sintering resistance, and can solve the technical problems of poor high-temperature phase stability of existing thermal barriers, high thermal conductivity of coatings, and poor sintering resistance. In addition, the material can also be directly sprayed on the surface of other coatings for thermal protection, and has a wide range of applications.

[0017] The low thermal conductivity anti-sintering thermal barrier coating provided by the present invention is formed by spraying the low thermal conductivity anti-sintering thermal barrier coating material on the substrate or other coating surface. In the obtained coating, ZrO 2 The monoclinic phase content is less than 2%, the thermal conductivity is less than 0.7 W / (m·K) at room temperature to 225°C, and it has good sintering resistance at 1350°C for 20 hours. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Schematic diagram of low- and high-magnification surface SEM morphology of the low thermal conductivity anti-sintering thermal barrier coating material of Example 1 of the present invention; wherein A is 1000×, and B is 2000×; Figure 2 This is a schematic diagram of the particle size distribution of the low thermal conductivity anti-sintering thermal barrier coating material according to Example 1 of the present invention; Figure 3 XRD patterns of the low thermal conductivity anti-sintering thermal barrier coating material (RSZ4Y powder) and the thermal barrier coating (RSZ4Y coating) prepared using the same according to Example 1 of the present invention; Figure 4 This is a schematic diagram showing the comparison of thermal conductivities of the low thermal conductivity anti-sintering thermal barrier coating material and the thermal barrier coating prepared using the low thermal conductivity thermal barrier coating material according to Example 1 of the present invention at room temperature to 225° C.; Figure 5The low thermal conductivity sintering-resistant thermal barrier coating material and the thermal barrier coating prepared using the same according to Example 1 of the present invention are observed at a magnification of 10000 times before and after sintering at 1350°C for 20 h; wherein A is the morphology of the RSZ4Y coating before sintering, B is the morphology of the YSZ coating before sintering, C is the morphology of the RSZ4Y coating after sintering at 1350°C for 20 h, and D is the morphology of the YSZ coating after sintering at 1350°C for 20 h; Figure 6 This is a comparison chart of the porosity changes of the low thermal conductivity sintering-resistant thermal barrier coating material and the thermal barrier coating prepared using the low thermal conductivity sintering-resistant thermal barrier coating material according to Example 1 of the present invention at 1350° C. and different sintering times; Figure 7 This is a morphology image of a 200 μm thick low thermal conductivity anti-sintering thermal barrier coating of Example 2 of the present invention observed in SE mode of an electron microscope at 15000 times magnification; Figure 8 The XRD spectrum of the 50 μm thick low thermal conductivity anti-sintering thermal barrier coating in Example 2 of the present invention; Fig. 9 This is a comparison chart of the reflectivity of the RSZ4Y coating prepared in Example 2 of the present invention and the control YSZ coating and RSZ coating. DETAILED DESCRIPTION

[0019] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0020] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0021] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0022] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0023] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0024] The present invention provides a low thermal conductivity anti-sintering thermal barrier coating material, comprising 82.3 mol% to 92.45 mol% of zirconium oxide (ZrO 2 )、3.5 mol%~7.5 mol% yttrium oxide (Y 2 O 3 ), 2.0 mol%~3.0 mol% ytterbium oxide (Yb 2 O 3 ), 1.5 mol%~4.0 mol% gadolinium oxide (Gd 2 O 3 ), 0.5 mol%~2.0 mol% neodymium oxide (Nd 2 O 3 ) and 0.05 mol%~1.2 mol% of aluminum oxide (Al 2 O 3 ); Among them, the main stable oxide Y 2 O 3 and rare earth dopant Yb 2 O 3 , Gd 2 O 3 and Nd 2 O 3 They are present in the form of solid solution in the matrix oxide ZrO 2 In the formation of ZrO 2 Solid solution; Al 2 O 3 It is doped into ZrO as a second phase 2 In solid solution; Al 2 O 3 The particle size of the raw material is 0.75~1.25 μm; Gd 2 O 3 and Nd 2 O 3 The sum of the molar percentages of Yb 2 O 3 The molar percentage ratio is 1.0~2.0; the low thermal conductivity anti-sintering thermal barrier coating material is a nearly spherical powder of 10~145 μm.

[0025] The above-mentioned low thermal conductivity anti-sintering thermal barrier coating material has the following characteristics: (1) Stable phase and mechanical properties.2 O 3 and rare earth dopant Yb 2 O 3 The tetravalent cations have lower solid solubility energy in the oxygen vacancy compensation of oxides. Based on the principle of electrical neutrality, it is easier to form a ZrO matrix oxide. 2 A large number of oxygen vacancies are formed in the material, and the repulsive force between local oxygen and oxygen is reduced, so that the coordination layer is greatly distorted, the interlayer stress is released, and the material can maintain the cubic and tetragonal phases at room temperature; among them, the large-particle trivalent dopant cation Y 3+ and Yb 3+ Smaller trivalent dopant cations have a cation-to-anion ratio greater than 0.732 (O 2- ) has a greater tendency to form 8-coordinates, which is more effective in stabilizing tetragonal and cubic ZrO 2 The crystal structure is better, Nd 3+ and Gd 3+ The larger lattice distortion caused by Zr helps stabilize the cubic phase; at the same time, the point defects brought by the highly coordinated and smaller radius cations will also weaken the driving force generated in the tetragonal phase region, which is similar to Zr 4+ Y of similar size 3+ and Yb 3+ Can enter ZrO 2 In the lattice, the transformation of the tetragonal phase is suppressed, and finally the phase is kept stable at both high and low service temperatures. 2 O 3 and Yb 2 O 3 The amount of two groups of oxides is reduced by adding, among which Yb 2 O 3 The increase of Gd is conducive to the production of more tetragonal phases, and excessive doping will destroy the stability of the crystal. Therefore, based on experimental data and the need for high temperature phase stability, 2 O 3 and Nd 2 O 3 In terms of physical and chemical properties, Yb 2 O 3 The doping amount of Gd 2 O 3 、Nd 2 O 3 The ratio of the sum of the doping amounts needs to be kept within the range of 1 to 2.0. 2 In solid solution, Yb 2 O 3 The solid solubility limits of Yb are about 2.4 mol% and 8.0 mol%, respectively. Combined with the limited proportion of the cubic phase, 2 O 3The doping amount is selected in the range of 2.0~3.0 mol%. If it is too low, it will affect the phase stability. It is important that the total amount of quaternary oxide doping needs to be controlled to achieve the coordination of phase stability and other properties such as thermal conductivity. For the critical oxygen vacancies, since the quaternary doped oxide cations in the formula are all tetravalent and lack the stabilization of tetravalent / pentavalent cations, the total amount of doped oxides must also be within the range defined in the formula. If there are too few oxygen vacancies after doping, it will not stabilize the phase and promote cluster formation and reduce thermal conductivity. If there are too many oxygen vacancies, many free oxygen vacancies will easily migrate from the interior to the interface at high temperatures, resulting in the weakening of phase stability at high temperatures and mechanical properties at service temperature. Refer to Zr 2 O 3 -Y 2 O 3 Phase diagram and service temperature requirements above 1500℃, Y 2 O 3 The doping amount needs to be at least 3.5 mol%, and the total doping amount of solid solution doping is not higher than 16.5 mol%. As a second phase dopant, Al 2 O 3 Doping in it can improve the fracture toughness of the material. 2 O 3 It can improve the sintering performance, and its doping range needs to be controlled and maintained within the range of 0.05~1.2 mol% to ensure the optimal performance of the material.

[0026] (2) Low thermal conductivity and sintering resistance. 2 O 3 , Yb 2 O 3 , Gd 2 O 3 and Nd 2 O 3 Solid solution doping of four types of rare earth oxides will be 2 Large lattice distortion and oxygen vacancies are generated inside the lattice, and Y with different radii at different positions in the internal sublattice 3+ , Gd 3+ and Yb 3+ The interaction between the two will lead to the generation of special defect clusters, which further enhances the stability of the lattice; rare earth cations, oxygen vacancies, and defect clusters of different sizes and atomic masses enhance phonon diffusion, thereby reducing thermal conductivity. The pinning of oxygen vacancies and the stabilization of clusters improve the sintering resistance of the material; Al 2 O 3 The second phase doping provides the material with photon scattering ability at high temperature, reduces the overall thermal conductivity of the material at high temperature and balances the performance of sintering resistance and low thermal conductivity at high temperature. 2 O 3 and Yb 2O 3 Two groups, compared with the main stable oxide cation Y 3+ Rare earth cation doping with larger and smaller radius sizes can effectively produce lattice distortion, thereby enhancing phonon scattering. Based on the principle of electrical neutrality, doping cations and oxygen vacancies can produce stable high-concentration defects, promote ion defect segregation and the formation of defect clusters, reduce the flow defect concentration, and thus improve sintering resistance; Gd 2 O 3 and Yb 2 O 3 Both groups also have larger oxide formation free energy, which makes the defect clusters more stable, thereby reducing thermal conductivity and improving sintering resistance. 2 O 3 It has a larger bond population and plays a greater role in stabilizing the clusters. Experimental data show that its doping amount needs to be less than 3.0 mol% to maintain a balance between thermal conductivity and lattice stability. If it is too little, there will be insufficient vacancies and the clusters will not be stable. If it is too much, it will destroy the existing lattice stability. 2 O 3 Because of its larger size close to that of oxygen ions (Nd 3+ The size is larger than Zr 4+ If the Nd content is greater than 15%, it will strongly destroy the lattice degree, thereby promoting the formation of defect clusters. The highly distorted lattice structure produced can enhance phonon diffusion and inhibit atomic migration, thereby improving the sintering resistance. 2 O 3 In ZrO 2 Analysis of the doping amount used in the experiment and the actual experimental data, Nd 2 O 3 The content of Yb needs to be controlled at 0.5~2.0 mol%, which will help reduce thermal conductivity, promote cluster formation, inhibit grain growth, improve phase stability and increase thermal expansion coefficient. Its own doping solid solution amount is limited, and too high a content is not conducive to the stable existence of clusters. 2 O 3 The doping amount of Gd 2 O 3 、Nd 2 O 3 The ratio of the sum of the doping amounts needs to be kept within the range of 1.0 to 2.0. 2 O 3 The content of MgO is between 1.5 and 4.0 mol%, and its advantage of strongly reducing the thermal conductivity of the material is not affected.

[0027] The five-element doped ZrO in the present invention 2 Compared with other binary, ternary, quaternary, and quinary doped ZrO 2First, they have unique doping components and component ratios. The four types of solid solution dopants all have unique cation sizes and oxide formation free energies, which are similar to Zr 4+ More lattice dislocations will be generated between the cations of other dopants, which will introduce more vacancies and lattice distortions inside the material and promote the precipitation of stable defect clusters, making the five-element doped ZrO 2 It has more and more stable defect cluster structures. Secondly, the quantitative ratio of dopants makes nanoclusters evenly distributed inside the material; by optimizing the molar ratio of the main stabilizer and four types of solid solution dopants, the determined composition range allows dopants of different types and doses to be co-doped and coordinated inside the material, resulting in stable clusters and highly distorted lattice structures, which effectively intensifies the phonon scattering and inhibits atomic migration inside the material, ultimately reducing the thermal conductivity inside the material and improving the sintering resistance. Second-phase doping intensifies the photon scattering on the surface of the material in a high-temperature environment, thereby reducing the overall thermal conductivity of the material, controlling the second-phase doping ratio, improving fracture toughness, and taking into account both sintering resistance and overall low thermal conductivity.

[0028] The present invention also provides a method for preparing the above-mentioned low thermal conductivity anti-sintering thermal barrier coating material, comprising: adding 82.3 mol% to 92.45 mol% of ZrO 2 , 3.5 mol%~7.5 mol% Y 2 O 3 , 2.0 mol%~3.0 mol% Yb 2 O 3 , 1.5 mol%~4.0 mol% Gd 2 O 3 and 0.5 mol%~2.0 mol% Nd 2 O 3 The premixed powder is then mixed with 0.05 mol% to 1.2 mol% Al2O3 with a particle size range of 0.75 to 1.25 μm. 2 O 3 Mix and grind, and prepare low thermal conductivity anti-sintering thermal barrier coating material by solid phase sintering method. The specific steps are as follows: Step 1. Select Y 2 O 3 , Yb 2 O 3 , Gd 2 O 3 and Nd 2 O 3 As a solid solution dopant, 3.5 mol% to 7.5 mol% Y 2 O 3 , 2.0 mol%~3.0 mol% Yb 2 O3 , 1.5 mol%~4.0 mol% Gd 2 O 3 and 0.5 mol%~2.0 mol% Nd 2 O 3 powder, with 82.3 mol%~92.45 mol% ZrO 2 The powders were mixed to obtain a mixed powder of gadolinium oxide-yttrium oxide-ytterbium oxide-neodymium oxide. The mixed powder of gadolinium oxide-yttrium oxide-ytterbium oxide-neodymium oxide was placed in a zirconia ball milling jar by wet ball milling, using zirconia balls and anhydrous ethanol as the dispersion medium. The mass ratio of powder: ball: medium was 1:2:3, and the mixture was ball milled at a speed of 250-300 r / min for 3-4 h in a high-energy ball mill, and then dried at 70-100°C for 12-24 h to remove the anhydrous ethanol medium, and then ground after drying to obtain a premixed powder.

[0029] Step 2: Select Al with a particle size range of 0.75~1.25 μm 2 O 3 As the second phase dopant, 0.05 mol%~1.2 mol% Al was added to the premixed powder obtained in step 1. 2 O 3 The powders were mixed, and zirconia balls were used. The dispersion medium was anhydrous ethanol. The mass ratio of powder: ball: medium was 1:1:3. The mixture was ball-milled at a speed of 100-150 r / min for 30 min in a stirring ball mill. After drying, the mixture was ground to obtain a mixed powder.

[0030] Step 3: Use a desktop tablet press to cold isostatically press (40-60 MPa, 3 min) the mixed powder obtained in step 2 into a φ25 mm×4 mm disc, place the disc in a muffle furnace, and sinter it at 1400-1500℃ for 5-10 h without pressure to obtain a molded body. After the body is crushed, grind it again and filter it with a 100-mesh screen to finally obtain a uniform mixed powder in the range of 10-145 μm, that is, a low thermal conductivity anti-sintering thermal barrier coating material. Normal equipment cooling is used throughout the sintering process.

[0031] The present invention also provides a low thermal conductivity anti-sintering thermal barrier coating, wherein the mixed powder is sprayed on the surface of a substrate or a YSZ coating surface with a spraying thickness of 50 to 350 μm to obtain a low thermal conductivity anti-sintering thermal barrier coating; The spraying technology used during spraying includes but is not limited to atmospheric plasma spraying, vacuum plasma spraying or electron beam physical vapor deposition technology.

[0032] Below in conjunction with specific embodiment, further elaborate the present invention.Should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.In addition, should be understood that after reading the content of the present invention description, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall equally within the scope limited by the appended claims of the application.

[0033] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples, unless otherwise specified, are conventional commercial products, and their specifications are conventional specifications in the art.

[0034] Example 1 1. Preparation of low thermal conductivity anti-sintering thermal barrier coating material (RSZ4Y) Step 1: 89.35 mol% ZrO 2 、5.8 mol% Y 2 O 3 , 2.1 mol% Yb 2 O 3 , 2.1 mol% Gd 2 O 3 and 0.6 mol% Nd 2 O 3 The dosage of quaternary rare earth doped oxide (Gd 2 O 3 , Y 2 O 3 and Yb 2 O 3 The purity is 99.99%, Nd 2 O 3 The purity is 99%, purchased from Beijing Bailingwei) powder and ZrO 2 The powders were mixed to obtain a mixed powder of gadolinium oxide-yttrium oxide-ytterbium oxide-neodymium oxide-zirconia. Zirconia balls with a diameter of 6 mm were used, and anhydrous ethanol was used as the dispersion medium. According to the mass ratio of gadolinium oxide-yttrium oxide-ytterbium oxide-neodymium oxide-zirconia mixed powder: zirconium oxide balls: anhydrous ethanol of 1:2:3, each component was added to a zirconia ball milling jar, and ball milled at a speed of 300 r / min for 4 h in a high-energy ball mill, and then dried at 80°C for 18 h to remove the anhydrous ethanol medium, and then ground after drying to obtain a premixed powder.

[0035] Step 2: Add 0.05 mol% Al to the premixed powder obtained in step 1. 2 O 3The powder (particle size 0.75-1.25 μm, purity ≥99.5%, purchased from Guangzhou Xinxi Chemical) was mixed to obtain premixed powder-alumina powder. Zirconia balls with a diameter of 6 mm and anhydrous ethanol were used as the dispersion medium. The mass ratio of premixed powder-alumina powder: zirconium oxide balls: anhydrous ethanol was 1:1:3. The mixture was ball milled at a speed of 120 r / min for 30 min in a stirred ball mill, dried and ground to obtain a mixed powder.

[0036] Step 3: Use a desktop tablet press to cold isostatically press (40-60 MPa, 3 min) the mixed powder obtained in step 2 into a φ25 mm×4 mm disc, place the disc in a muffle furnace, and sinter at 1400°C for 8 h to obtain a formed green body. After the green body is crushed, it is ground again and filtered through a 100-mesh sieve to finally obtain a uniform RSZ4Y powder in the range of 10-145 μm.

[0037] The surface morphology of the prepared RSZ4Y powder was observed by scanning electron microscopy (SEM) at low and high magnifications. Figure 1 As shown in the figure, it can be seen that RSZ4Y powder is agglomerated and nearly spherical. 2 O 3 The doping amount is small, so no Al as a second phase is seen on the powder surface. 2 O 3 The particle size distribution of the RSZ4Y powder obtained is as follows: Figure 2 As shown, the particle size distribution is relatively concentrated and the range is in line with expectations.

[0038] 2. Preparation of low thermal conductivity anti-sintering thermal barrier coating The RSZ4Y powder prepared in step 1 was sprayed on the surface of the GH4169 substrate using an atmospheric plasma spraying process (power 45 kW, current 650 A, voltage 70 V, spraying distance 12 cm, and powder feeding rate of the ZB-80F powder feeder 6 r / min) to obtain a 300 μm thick RSZ4Y coating.

[0039] At the same time, thin-walled hollow spherical shell yttria-stabilized zirconia powder (Metco 204NS-G; purchased from Metco, USA) was used as the traditional material YSZ control group, and YSZ-204NS-G powder with a particle size of 40-90 μm was screened with a sieve. YSZ-204NS-G powder was sprayed on the same substrate using a similar spraying process (power 42 kW, current 600 A, voltage 70 V, spraying distance 10 cm, and powder feeding rate of ZB-80F powder feeder 5 r / min) to obtain a YSZ coating with porosity and thickness similar to RSZ4Y as a traditional control coating.

[0040] RSZ4Y powder and RSZ4Y coating were characterized by X-ray diffractometer. Figure 3 As shown, it can be seen that due to Yb 2 O 3 , Gd 2 O 3 and Nd 2 O 3 The doping amount is small, and the main component is c-ZrO 2 With Y 0.15 Zr 0.85 O 1.93 The M phase content in RSZ4Y powder and RSZ4Y coating is less than 2% according to the calculation of the M phase mass from the XRD diffraction peak. 2 O 3 The doping amount is small and is not obvious under XRD, which is consistent with the SEM result.

[0041] The ceramic layer was peeled off by acid washing the sample. The thermal conductivity of RSZ4Y coating and YSZ coating at 25℃ to 225℃ was tested by laser flash method. The test results are as follows: Figure 4 As shown in the figure, the thermal conductivity of RSZ4Y coating is 0.61 W / (m·K) at 25°C and 0.65 W / (m·K) at 200°C, both of which are lower than the thermal conductivity of YSZ coating at the same temperature (0.89 W / (m·K) and 0.91 W / (m·K). It can be seen that the thermal conductivity of the coating made by the material provided by this method is lower than that of traditional YSZ.

[0042] The samples sprayed with RSZ4Y coating and the samples sprayed with YSZ coating were pickled to remove the ceramic layer, and then kept at 1350℃ for 20 h to test the sintering resistance of RSZ4Y coating and YSZ coating. Figure 5 As shown in the figure, after sintering, the internal pore cracks of RSZ4Y coating and YSZ coating gradually healed, and the unmelted particles showed neck connection phenomenon. Under the same conditions, the YSZ coating was denser, indicating that the RSZ4Y coating was more sintering-resistant than the YSZ coating.

[0043] The pores of each coating section were characterized by SEM technology, and the image software was used for data processing to detect the changes in the internal porosity of the RSZ4Y coating and the YSZ coating. The test results are shown in Figure 6. It can be seen that under the same sintering conditions, the porosity decrease rate of the RSZ4Y coating is lower than that of the YSZ coating, indicating that the RSZ4Y coating has better sintering resistance than the YSZ coating.

[0044] Example 2 The difference from Example 1 is that the powder ratio and the spraying thickness of the coating are different.

[0045] 1. Preparation of low thermal conductivity anti-sintering thermal barrier coating material (RSZ4Y) Weigh 82.3 mol% ZrO 2 、7.5 mol% Y 2 O 3 , 3.0 mol% Yb 2 O 3 , 4.0 mol% Gd 2 O 3 , 2.0 mol% Nd 2 O 3 and 1.2 mol% Al 2 O 3 , refer to the method of Example 1 to prepare RSZ4Y powder.

[0046] In addition, the same preparation method was used to prepare 2 O 3 The RSZ powder with the other components in the same relative proportion was used as the control powder.

[0047] 2. Preparation of low thermal conductivity anti-sintering thermal barrier coating The RSZ4Y powder prepared in step 1 was sprayed on the surface of the GH4169 substrate with different thicknesses (50 μm, 200 μm and 350 μm) using an atmospheric plasma spraying process (power 45 kW, current 650 A, voltage 70 V, spraying distance 12 cm, and powder feeding rate of the ZB-80F powder feeder 6 r / min) to obtain three groups of RSZ4Y coatings. The high-magnification SEM morphology of the coating with a thickness of 200 μm is shown in Figure 2. Figure 7 As shown, Al around 1 μm can be seen 2 O 3 Particles embedded in doped ZrO 2 In the experiment, the interface is clear, without cracks and particle aggregation.

[0048] The three groups of RSZ4Y coatings were characterized by X-ray diffractometer. The results showed that the XRD patterns of the three groups of coatings with different thicknesses did not change with thickness. The XRD pattern of the 50 μm RSZ4Y coating was as follows: Figure 8 As shown in the figure, it can be seen that with the increase of thickness, the XRD phase composition does not change, and only a very small amount of α-Al 2 O 3 The presence of diffraction peaks. Analysis of the phase composition of three groups of RSZ4Y coating XRD, ZrO 2 The main components are c-ZrO 2 With Y 0.15 Zr 0.85 O 1.93The M phase content was calculated from the XRD diffraction peak and was less than 2%, which did not change with the thickness. The above results show that the spraying thickness of the coating does not affect the structural composition of the coating.

[0049] The three groups of RSZ4Y samples were pickled and the RSZ4Y coatings were peeled off. The thermal conductivity of the three groups of RSZ4Y coatings of different thicknesses at room temperature was detected by the laser flash method. The results showed that the thermal conductivity of the three groups of coatings was maintained at around 0.68 W / (m·K), which was higher than 0.61 W / (m·K) in Example 1. After sintering at 1500°C for 10 h, although the thermal conductivity of the coating increased to 0.89W / (m·K), it was still not higher than the thermal conductivity of the YSZ coating at room temperature in Example 1, and had lower thermal conductivity and better sintering resistance. The above results show that under the same preparation and testing conditions, the increase in the content of the four groups of solid solution doped oxides will only further reduce the thermal conductivity of the material; but the second phase Al 2 O 3 It has a high thermal conductivity. Its doping will naturally increase the thermal conductivity of the material, and its own properties will also promote the sintering of the coating, thereby continuing to increase the phonon thermal conductivity during use. Compared with Example 1, more Al 2 O 3 The effect of the doping amount on the phonon thermal conductivity is slightly greater than the effect of more rare earth oxide doping on the thermal conductivity, but rare earth doping is still effective in improving the sintering resistance, and the thermal conductivity after sintering is not too high.

[0050] 3. Test Al 2 O 3 Optical effects of particles in coatings YSZ-204NS-G powder, RSZ powder and RSZ4Y powder were used to prepare 200 μm thick YSZ coating, RSZ coating and RSZ4Y coating respectively by using their own process technology (RSZ spraying technology is the same as RSZ4Y), and the coating was peeled off by pickling. The reflectivity of the three coatings in the wavelength range of 300~2000 nm was tested by UV-VIS-NIR spectrophotometer UV-3600 at room temperature. The test results are shown in Fig. 9 As shown, the reflectivity of RSZ coating is similar to that of YSZ coating, while RSZ4Y coating exhibits a greater reflectivity in both visible light and near-infrared wavelength ranges (greater than 1 / 6 of the reflectivity of conventional coatings), which helps to reduce heat transfer mainly by thermal radiation at high temperatures, and by reducing photon thermal conductivity, it has an overall low thermal conductivity performance at high temperatures.

[0051] Example 3 The difference from Example 1 is that the powder ratio and the powder particle size are different, and the particle size range is 10-75 μm.

[0052] 1. Preparation of low thermal conductivity anti-sintering thermal barrier coating material (RSZ4Y) Weigh 87.7 mol% ZrO 2 , 6.5 mol% Y 2 O 3 , 2.3 mol% Yb 2 O 3 , 2.2 mol% Gd 2 O 3 , 1.0 mol% Nd 2 O 3 and 0.3 mol% Al 2 O 3 RSZ4Y powder was prepared by referring to the method of Example 1. The powder with a particle size range of 10-75 μm was screened with a sieve to obtain the desired RSZ4Y powder.

[0053] 2. Preparation of low thermal conductivity anti-sintering thermal barrier coating The RSZ4Y powder prepared in step 1 was sprayed on the surface of the GH4169 substrate using an atmospheric plasma spraying process (power 45 kW, current 650 A, voltage 70 V, spraying distance 12 cm, and powder feeding rate of the ZB-80F powder feeder 6 r / min) to obtain a 300 μm RSZ4Y coating.

[0054] The obtained RSZ4Y coatings were characterized by X-ray diffractometer. No α-Al 2 O 3 The presence of obvious diffraction peaks indicates that the main components are c-ZrO 2 With Y 0.15 Zr 0.85 O 1.93 By calculating the mass of M phase from the XRD diffraction peak, it can be seen that the content of M phase in this group of coating phases is less than 2%.

[0055] The sample was pickled to peel off the ceramic layer. The thermal conductivity of the RSZ4Y coating at room temperature was detected by laser flash method, and it was found that the thermal conductivity of the coating was about 0.65 W / (m·K), which was higher than the thermal conductivity of the RSZ4Y coating in Example 1 (0.61 W / (m·K)), but still lower than the thermal conductivity of the traditional YSZ coating in Example 1 (0.89 W / (m·K)). Combined with the porosity statistics, it shows that the RSZ4Y coating prepared by this composition and method still has good heat resistance.

[0056] The RSZ4Y coating peeled off by pickling was placed in a muffle furnace and kept at 1300℃ for 20 h to test the sintering resistance of the RSZ4Y coating. The pores of each coating section were characterized by SEM technology, and the image software was used for data processing to detect the change in the internal porosity of the RSZ4Y coating. The test results showed that the internal porosity of the sprayed coating was 5.5%, and after sintering at 1300℃ for 20 h, the porosity dropped to 4.8%. Figure 6 , the porosity after sintering can be seen to decrease less, reflecting better heat resistance and better sintering resistance.

[0057] Example 4 The difference from Example 1 is that the powder ratio and the powder particle size are different, and the particle size range is 75-145 μm.

[0058] 1. Preparation of low thermal conductivity anti-sintering thermal barrier coating material (RSZ4Y) Weigh 87.5 mol% ZrO 2 , 7.1 mol% Y 2 O 3 , 2.2 mol% Yb 2 O 3 , 1.5 mol% Gd 2 O 3 , 1.2 mol% Nd 2 O 3 and 0.1 mol% Al 2 O 3 , RSZ4Y powder was prepared by referring to the method of Example 1, and the powder with a particle size range of 75~145 μm was screened with a sieve.

[0059] 2. Preparation of low thermal conductivity anti-sintering thermal barrier coating The RSZ4Y powder prepared in step 1 was sprayed on the surface of the GH4169 substrate using an atmospheric plasma spraying process (power 45 kW, current 650 A, voltage 70 V, spraying distance 12 cm, and powder feeding rate of the ZB-80F powder feeder 6 r / min) to obtain a 300 μm RSZ4Y coating.

[0060] The obtained RSZ4Y coatings were characterized by X-ray diffractometer. The XRD analysis results showed that no α-Al 2 O 3 Obvious diffraction peaks, the main components are c-ZrO 2 and Y 0.15 Zr 0.85 O 1.93 By calculating the mass of the M phase from the XRD diffraction peak, it can be seen that the content of the M phase inside the coating phase is less than 2%.

[0061] The sample was pickled to remove the ceramic layer. The thermal conductivity of the RSZ4Y coating at room temperature was detected by laser flash method, and it was found that the thermal conductivity of the coating was about 0.51 W / (m·K), which was lower than the thermal conductivity of the RSZ4Y coating in Example 1 (0.61 W / (m·K)) and lower than the thermal conductivity in Example 3 (0.65 W / (m·K)).

[0062] The pores of each coating cross section were characterized by SEM technology, and Image software was used for data processing to detect the change in the internal porosity of the RSZ4Y coating. It was found that the internal porosity of the coating was 7.8%, compared with the porosity of Example 3 (5.5%). Under the same spraying conditions, the larger the powder particle size, the more unmelted particles and pores there are, and the greater the porosity, which in turn leads to a further decrease in thermal conductivity. The coating made with a smaller particle size will have a denser structure, and the reduction in voids will lead to an increase in thermal conductivity.

[0063] The RSZ4Y coating peeled off by pickling was placed in a muffle furnace and kept at 1500℃ for 20 h to test the sintering resistance of the RSZ4Y coating. It was found that after sintering at 1500℃ for 20 h, the porosity dropped to 6.3%, which was lower than that of Example 1. Figure 6 , it can be seen that the decrease is small, reflecting better heat resistance and better sintering resistance.

[0064] Example 5 1. Preparation of low thermal conductivity anti-sintering thermal barrier coating material (RSZ4Y) Weigh 91.9 mol% ZrO 2 , 3.5 mol% Y 2 O 3 , 2.0 mol% Yb 2 O 3 , 1.5 mol% Gd 2 O 3 , 0.5 mol% Nd 2 O 3 and 0.6 mol% Al 2 O 3 , refer to the method of Example 1 to prepare RSZ4Y powder.

[0065] 2. Preparation of dual-layer ceramic low thermal conductivity anti-sintering thermal barrier coating (RSZ4Y+YSZ) The atmospheric plasma spraying process (power 36 kW, current 550 A, voltage 65 V, spraying distance 11 cm, powder feeding rate of ZB-80F powder feeder 6 r / min) was used to spray NiAlCoCrSiY powder (purchased from Beijing Yijin New Material Technology Co., Ltd.; Lot NO: GDTWJHA1909, particle size 15~75 μm, specific composition: Al is 11.0 wt%~14.0wt%, Co is 20.0 wt%~26.0 wt%, Cr is 14.0 wt%~20.0 wt%, Si is 0.1 wt%~0.8 wt%, Y is 0.1wt%~0.8 wt%, and the rest is Ni) on the substrate surface to prepare a bonding layer with a thickness of 40 μm. Then, an atmospheric plasma spraying process (power 42 kW, current 600 A, voltage 70 V, spraying distance 10 cm, and powder feeding rate of ZB-80F powder feeder 5 r / min) was used to spray a layer of YSZ coating (formed by YSZ-204NS-G) with a thickness of about 100 μm on the surface of the bonding layer, and then an atmospheric plasma spraying technology (power 45 kW, current 650 A, voltage 70 V, spraying distance 12 cm, and powder feeding rate of ZB-80F powder feeder 6 r / min) was used to spray a layer of RSZ4Y coating prepared in step 1 with a thickness of 150 μm on the surface of the YSZ coating to obtain a double ceramic layer thermal barrier coating.

[0066] After tensile testing with a universal testing machine, the bonding strength of the double-ceramic layer thermal barrier coating was 22.5±2 MPa, the fracture was located at the interface between the bonding layer and the YSZ layer, and the YSZ-RSZ4Y interface was well bonded.

[0067] The double ceramic layer thermal barrier coating was characterized by X-ray diffractometer. The XRD analysis results showed that there was no obvious α-Al 2 O 3 Diffraction peaks, the main components are c-ZrO 2 and Y 0.15 Zr 0.85 O 1.93 By calculating the mass of the M phase from the XRD diffraction peak, it can be seen that the M phase content inside the top RSZ4Y coating phase is less than 2%.

[0068] The sample was pickled and the double ceramic layer thermal barrier coating was peeled off. The thermal conductivity of the double ceramic layer thermal barrier coating at room temperature was detected by laser flash method, and it was found that the thermal conductivity of the double ceramic layer thermal barrier coating was about 0.78 W / (m·K), which was lower than the traditional YSZ coating in Example 1.

[0069] The peeled dual-ceramic layer thermal barrier coating was placed in a muffle furnace and kept at 1500℃ for 10 hours to test the sintering resistance of the dual-ceramic layer thermal barrier coating. After SEM observation of the coating cross section and image software data processing and analysis, it was found that the YSZ layer showed a faster sintering rate, and the top layer RSZ4Y still showed better sintering resistance than traditional YSZ.

[0070] The above results show that the low thermal conductivity anti-sintering thermal barrier coating prepared by this method can be directly sprayed on the surface of the substrate for thermal protection, and can also be directly sprayed on the surface of other coatings for thermal protection, and has a wider range of applications.

[0071] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A low thermal conductivity anti-sintering thermal barrier coating material, characterized in that: In terms of mole percentage, it includes 82.3% to 92.45% ZrO2, 3.5% to 7.5% Y2O3, 2.0% to 3.0% Yb2O3, 1.5% to 4.0% Gd2O3, 0.5% to 2.0% Nd2O3 and 0.05% to 1.2% Al2O3; Among them, Y2O3, Yb2O3, Gd2O3 and Nd2O3 all exist in ZrO2 in the form of solid solution to form ZrO2 solid solution, and Al2O3 is doped in the ZrO2 solid solution in the form of a second phase; the ratio of the sum of the molar percentages of Gd2O3 and Nd2O3 to the molar percentage of Yb2O3 is 1.0~2.0; the particle size of Al2O3 is 0.75~1.25 μm.

2. The low thermal conductivity anti-sintering thermal barrier coating material according to claim 1, characterized in that: In the ZrO2 solid solution, the content of ZrO2 monoclinic phase is less than 2.0%.

3. A low thermal conductivity anti-sintering thermal barrier coating material according to claim 1 or 2, characterized in that: The low thermal conductivity anti-sintering thermal barrier coating material is a nearly spherical powder with a particle size of 10~145 μm.

4. The method for preparing a low thermal conductivity anti-sintering thermal barrier coating material according to any one of claims 1 to 3, characterized in that: After ZrO2, Y2O3, Yb2O3, Gd2O3 and Nd2O3 powders are mixed, ball milling and grinding are performed for the first time to obtain premixed powders; Al2O3 powder is added to the premixed powders and mixed, ball milling and grinding are performed for the second time to obtain mixed powders, and then low thermal conductivity sintering-resistant thermal barrier coating materials are prepared by solid phase sintering method.

5. The method for preparing a low thermal conductivity anti-sintering thermal barrier coating material according to claim 4, characterized in that: Wet ball milling was adopted, zirconia balls were used in the ball milling process, and anhydrous ethanol was used as the dispersion medium.

6. The method for preparing a low thermal conductivity anti-sintering thermal barrier coating material according to claim 4, characterized in that: The conditions for the first ball milling were: ball milling at a speed of 250-300 r / min for 3-4 h; the conditions for the second ball milling were: ball milling at a speed of 100-150 r / min for 30 min.

7. A low thermal conductivity anti-sintering thermal barrier coating, characterized in that: The low thermal conductivity anti-sintering thermal barrier coating material according to any one of claims 1 to 3 is sprayed on a substrate or other coating surface to form the coating.

8. The low thermal conductivity anti-sintering thermal barrier coating according to claim 7, characterized in that: The thickness of the low thermal conductivity anti-sintering thermal barrier coating is 50~350 μm.

9. The low thermal conductivity anti-sintering thermal barrier coating according to claim 7, characterized in that: The thermal conductivity of the low thermal conductivity anti-sintering thermal barrier coating is less than 0.7 W / (m·K) at 25℃~225℃.

10. Use of a low thermal conductivity anti-sintering thermal barrier coating according to any one of claims 7 to 9 in thermal protection of an aircraft engine turbine, a rocket engine tail nozzle or a rocket engine combustion chamber.

Citation Information

Patent Citations

  • Ternary rare earth doped YSZ thermal barrier coating material and preparation method thereof

    CN106588042A

  • High-purity, stable-phase and anti-sintering zirconia-based coating and preparation method thereof

    CN119121112A

  • Thermal Barrier Coating Materials and Method forMaking the Same, and Method for Forming the ThermalBarrier Coating Layers

    KR1020020010842A

  • Low Thermal Conductivity, CMAS-Resistant Thermal Barrier Coatings

    US20090184280A1

Cited By

  • High-temperature environment barrier / thermal barrier / electromagnetic shielding multifunctional composite coating and preparation method thereof

    CN121450135A